The Nature and Practices of Social Justice in the View of Sayyid Qutb (Jurnal Pembangunan Sosial, 2009)
This paper discusses the nature of social justice as enunciated by Sayyid Qutb, an Egyptian prominent scholar in the 1960s. Failure of the political system, economic disparity, coupled with the British interference in many aspects of Egyptian socio-political life led to the so called ‘Egyptian disillusionment’ with the existing problems facing their country. Qutb’s notion of social justice is all embracing; spiritual and material life, and is not merely limited to economic justice. Together with other Egyptian intellectuals like Najib Mahfuz, Muhammad al-Ghazali, and Imad al-Din Abd al-Hamid, Sayyid Qutb managed to propose some alternative solutions in the form of writings including that of books and journal articles. Some major issues discussed in Sayyid Qutb’s works:’al-Adalah al-Ijtimaiiyah fil Islam, Ma’rakat al-Islam wal Ra’samaliyyah and his article al-Fikr al-Jadid, will then be analyzed as to see their importance in articulating some social solutions in a practical and realistic manner, in true accord both with the spirit of Islam and the contemporary human situation.